Antimicrobial peptide Hs02 with rapid bactericidal, anti-biofilm, and anti-inflammatory activity against carbapenem-resistant Klebsiella pneumoniae and Escherichia coli - Deyi Zhao; Miran Tang; Panjie Hu; Xiaowei Hu; Weijun Chen; Zhexiao Ma; Huanchang Chen; Haifeng Liu; Jianming Cao; Tieli Zhou (Microbiology Spectrum)
ABSTRACT Carbapenem-resistant Klebsiella pneumoniae (CRKP) and Escherichia coli (CREC) are frequently detected in clinical settings, restricting the use of carbapenems. Therefore, there is an urgent need for new antimicrobial strategies to address infections caused by CRKP and CREC. This study investigated the antibacterial, anti-biofilm, and anti-inflammatory effects of the cationic antimicrobial peptide Hs02, along with its potential antimicrobial mechanisms against CRKP and CREC. The results revealed that Hs02 had a low minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against CRKP and CREC, effectively eliminating the bacteria within 30 min. Moreover, Hs02 significantly prevents biofilm formation and disrupts the established biofilms. Further mechanistic studies demonstrated that Hs02 specifically targeted and bound to bacterial outer membrane lipopolysaccharides (LPS), disrupted membrane permeability and integrity, which led to intracellular reactive oxygen species (ROS) accumulation. Furthermore, Hs02 neutralized LPS, thereby suppressing the production of pro-inflammatory cytokines TNF-α, IL-6, and IL-1β in murine macrophage RAW 264.7 cells. In vitro, hemolysis and cytotoxicity assays confirmed Hs02’s safety at the tested concentrations and proved that Hs02 improved the survival rate of Galleria mellonella larvae. In conclusion, the findings suggest that Hs02’s interaction with LPS and the resulting disruption of membrane integrity may be key factors driving its rapid bactericidal and anti-inflammatory effects.IMPORTANCEEukaryotic antimicrobial peptides are typically amphipathic peptides consisting of approximately 50 amino acids. Many macromolecular proteins in our body contain polypeptide sequences that show characteristics similar to those of antimicrobial peptides. The present research highlights a gap in the current literature regarding the mechanisms by which the intragenic antimicrobial peptide Hs02, derived from human proteins, exerts its rapid bactericidal and anti-inflammatory effects. The findings demonstrate that lipopolysaccharide (LPS) is a key target of Hs02’s antimicrobial activity and that its ability to neutralize LPS is crucial for its anti-inflammatory effects.